2008
DOI: 10.1016/j.exer.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Topical interleukin-1 receptor antagonist inhibits inflammatory cell infiltration into the cornea

Abstract: Interleukin (IL)-1α and β are important modulators of many functions of corneal epithelial and stromal cells that occur following injury to the cornea, including the influx of bone marrow-derived inflammatory cells into the stroma attracted by chemokines released from the stroma and epithelium. In this study, we examined the effect of topical soluble IL-1 receptor antagonist on bone marrowderived cell influx following corneal epithelial scrape injury in a mouse model. C57BL/6 mice underwent corneal epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…17,18 Interestingly, topical application of IL-1Ra was shown to inhibit inflammatory cell infiltration into the cornea, but its effect on epithelial wound closure was not reported. 19 In the skin, IL-1Ra has been implicated in skin wound healing and fibrosis, with evidence of reduced skin fibrosis after application of anakinra, human recombinant IL-1Ra. 20,21 The role(s) of IL-1 and IL-1Ra in reepithelialization, particularly their unbalanced production in DM tissues, remains elusive.…”
mentioning
confidence: 99%
“…17,18 Interestingly, topical application of IL-1Ra was shown to inhibit inflammatory cell infiltration into the cornea, but its effect on epithelial wound closure was not reported. 19 In the skin, IL-1Ra has been implicated in skin wound healing and fibrosis, with evidence of reduced skin fibrosis after application of anakinra, human recombinant IL-1Ra. 20,21 The role(s) of IL-1 and IL-1Ra in reepithelialization, particularly their unbalanced production in DM tissues, remains elusive.…”
mentioning
confidence: 99%
“…PA treated mice showed significant NF-κB binding activity when compared to control group in both ear and back skin. On the contrary, 145 Books MDPI NF-κB binding activity in TECA treated mice was significantly inhibited when compared with PA treated mice ( Figures 3D and 4D). In addition, as shown in Figures 3E and 4E, PA treated mice showed significant IκBα degradation in cytosolic fraction when compared to the control group in both ear and back skin.…”
Section: Effect Of Teca On Nf-κb Dna Binding Activity In Pa-induced Amentioning
confidence: 93%
“…28 Topical application of IL-1 receptor antagonist inhibited inflammatory cells from infiltrating the cornea after epithelial injury. 26 IL-1 can also stimulate the production of other inflammatory mediators. Thus, Yang et al 29 reported that CXCL1, IL-6, and IL-8 (of the 36 molecules tested) were elevated after exposure to IL-1b in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important regulator of ocular surface inflammatory responses. [25][26][27] For example, after inhibiting the elevated IL-1b by anti-IL-1b antibody in Pseudomonas aeruginosa-induced ocular infections, the degree of corneal inflammation and rate of perforation were reduced by a reduction in the CXCL2 level and the number of PMN cells. 28 Topical application of IL-1 receptor antagonist inhibited inflammatory cells from infiltrating the cornea after epithelial injury.…”
Section: Discussionmentioning
confidence: 99%